Handbook of improving performance in the workplace. Volume 2, Selecting and implementing performance interventions - Watkins, Ryan.; Leigh, Doug. (San Francisco, Calif. : Jossey-Bass ; Chichester : John Wiley [distributor], 2010)
In this groundbreaking volume, leading practitioners and scholars from around the world provide an authoritative review of the most up-to-date information available on performance interventions, all presented within a holistic framework that helps ensure the accomplishment of significant results. Addressing more than 30 performance interventions, with such varied topics as Incentive Systems, e-Learning, Succession Planning and Executive Coaching, this volume guides readers through the development of comprehensive performance improvement systems. Each chapter illustrates in practical terms how to select, plan, implement, and manage performance interventions, as well as how to evaluate their results. Through best practices research, comparative analysis, illustrative case studies from around the world, and editorial guidance on how to link together diverse interventions, the handbook is an important guide for achieving desired results in the workplace and beyond. Sponsored by International Society for Performance Improvement (ISPI), the Handbook of Improving Performance in the Workplace, three-volume reference, covers three main areas of interest including Instructional Design and Training Delivery, Selecting and Implementing Performance Interventions, and Measurement and Evaluation.
Includes bibliographical references and index.
Print version record.
John Wiley and Sons
Keywords: Performance -- Management; Employees -- Training of; Performance technology -- Management; Rendement au travail -- Gestion; Personnel -- Formation; Employees -- Training of; Performance -- Management